Q: What is the factor of 2x plus 6y?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

(6,0) and (0,2)

Since y = 2, 2x + 6y is the same as 2x + 12. Because 2x + 12 = 22, 2x = 10. If 2 Xes are equal to ten, then 1 X is equal to 5.

no

The above expression simplifies to 2x-y+9z

Related questions

2(x - 3y + 7z)

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

20x2 + 22xy + 6y2 = 20x2 + 10xy + 12xy + 6y2 = 10x(2x + y) + 6y(2x + y) = (2x + y)(10x + 6y) = 2(2x + y)(5x + 3y)

the simplest form of 5x + 3y +2x - 6y is 7x-3y

6y2+17y-14 = (2x+7)(3x-2) when factored

It is (2x +y + 3)*(2x - y - 3).

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

(6,0) and (0,2)

5x + 6y + 3y - 2x you have to add like terms. add the y terms and then the x terms 9y + 3x this is your answer

6y

x(y - 10) + 6y

(3m2+4n)3